Evaluation Of The Effectiveness Of Government Food Security Programs From An Islamic Economic Perspective - Aas Fransiska; Romi Adetio Setiawan; Anwar Junaidi (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study explores the implementation and effectiveness of a food security program in Mekar Sari Village that provides duck and catfish livestock as part of efforts to strengthen local food resilience. The study seeks to fill the research gap concerning how Islamic economic principles can be applied to evaluate and enhance the sustainability of community-based food programs. Methodology: Using a qualitative field research approach, data were collected through interviews, observations, and documentation, and analyzed through the stages of data reduction, presentation, and conclusion drawing. Results: The findings indicate that the program effectively increases household income, food availability, and community self-reliance, while fostering values of solidarity, justice, and cooperation among residents. In addition, the study highlights that the program reflects core Islamic economic principles such as fairness, mutual assistance, and social welfare. Findings: However, improvements are still required in developing a fair profit-sharing system, integrating the program with productive zakat schemes, and enhancing Sharia-based financial literacy to optimize community welfare and ensure long-term program sustainability. Novelty & Originality: The novelty of this study lies in its integration of Islamic economic principles into the evaluation of a community-based food security program, an approach rarely undertaken in prior research. Its originality emerges from the application of Sharia-based values to assess program sustainability and community welfare outcomes in the Indonesian village context. Conclusions: These findings contribute to the growing discourse on Sharia-oriented development models and offer insights for policymakers in designing inclusive and ethically grounded food security initiatives. Type of Paper: This paper is Case study research paper.